The Involvement of CaV1.3 Channels in Prolonged Root Reflexes and Its Potential as a Therapeutic Target in Spinal Cord Injury - Jiang, Mingchen C.; Birch, Derin V.; Heckman, Charles J.; Tysseling, Vicki M. (Frontiers in Neural Circuits, 2021)
Spinal cord injury results in not only the loss of voluntary muscle control, but also in the presence of involuntary movement or spasms. These spasms post spinal cord injury (SCI) involve hyperexcitability in the spinal motor system. Hyperactive motor commands post SCI result from enhanced excitatory postsynaptic potentials and persistent inward currents in voltage-gated L-type calcium channels (LTCCs), which are reflected in evoked root reflexes with different timings. To further understand the contributions of these cellular mechanisms and to explore the involvement of LTCC subtypes in SCI-induced hyperexcitability, we measured root reflexes with ventral root recordings and motoneuron activities with intracellular recordings in an in vitro preparation using a mouse model of chronic SCI (cSCI). Specifically, we explored the effects of 1-(3-chlorophenethyl)-3-cyclopentylpyrimidine-2,4,6-(1H,3H,5H)-trione (CPT), a selective negative allosteric modulator of CaV1.3 LTCCs. Our results from the root recordings suggest that long-lasting reflexes (LLRs) has the strongest enhancement in cSCI mice. Bath application of CPT displayed slow onset but dose-dependent inhibition of the root reflexes with the strongest effect on LLRs. However, the inhibitory effect of CPT is less potent in cSCI mice than in acute SCI (aSCI) mice, suggesting changes either in composition of CaV1.3 or other cellular mechanisms in cSCI mice. For intracellular recordings, the intrinsic plateau potentials, was observed in more motoneurons in cSCI mice than in aSCI mice. CPT inhibited the plateau potentials and reduced motoneuron firings evoked by intracellular current injection. These results suggest that the LLR is an important target and that CPT has potential in the therapy of SCI-induced muscle spasms.